Supporting Students by Maintaining Professional Well-Being in High-Stress Jobs (LEARNing Landscapes, 2018)
Student mental health, well-being, engagement, and deep learning is tied to teacher wellness. Georgia State University’s Center for Research on School Safety, School Climate, and Classroom Management in partnership with The Collaboration and Resources for Encouraging and Supporting Transformations in Education project approached student health, wellness, and achievement by promoting change within teachers. Culturally specific professional development workshops were delivered to teachers, administrators, and other school staff. The workshops positively affected participants’ health and wellbeing through activities focused on identifying the body’s stress response and the development of personalized stress management plans to support healthy lifestyles.
Keywords: well-being, teacher wellness, professional development, teacher